Enhancing Tablet Product Experience on AliExpress: A Data-Driven Analysis of Online Customer Reviews - Isak, Mukhtar Adan; Laksono, Pringgo Widyo; Pujiyanto, Eko (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
In the competitive e-commerce landscape, understanding customer experience is critical for businesses to enhance satisfaction and drive sales, particularly for tablet products. This study provides in-depth insights into customer experiences with tablet products on the AliExpress platform by analyzing 4,469 online reviews through sentiment analysis and topic modeling. The sentiment analysis reveals that while a significant portion of reviews are neutral to slightly negative, the overall sentiment is positive, indicating general satisfaction. Topic modeling uncovers key themes, with positive discussions centered around fast delivery, value for money, and children's enjoyment, while negative themes highlight issues with screen performance, customs processes, and unexpected taxes, particularly for Brazilian customers. Temporal analysis shows dynamic spikes in topics like fast delivery and cost-benefit during specific periods. These findings provide actionable guidance for businesses and manufacturers to optimize tablet quality, logistics, and marketing strategies to meet the needs and preferences of their target audience better.